The disruption of JEN1 from Candida albicans impairs the transport of lactate - Silva, Isabel Soares (2004)
A lactate permease was biochemically identified in Candida albicans RM1000 presenting the following kinetic parameters at pH 5.0: Km 0.33 ± 0.09 mM and Vmax 0.85± 0.06 nmol s-1 mg dry wt-1. Lactate uptake was competitively inhibited by pyruvic and propionic acids; acetic acid behaved as a non-competitive substrate. An ORF homologous to Saccharomyces cerevisiae gene JEN1 was identified (CaJEN1). Deletions of both CaJEN1 alleles of C. albicans (resulting strain CPK2) resulted in the loss of all measurable lactate permease activity. No CaJEN1 mRNA was detectable in glucose-grown cells neither activity for the lactate transporter. In a medium containing lactic acid, CaJEN1 mRNA was detected in the RM1000 strain, and no expression was found in cells of CPK2 strain. In a strain deleted in the CaCAT8 genes the expression of CaJEN1 was significantly reduced, suggesting the role of this gene as an activator for CaJEN1 expression. Both in C. albicans and in S. cerevisiae cells CaJEN1-GFP fusion was expressed and targeted to the plasma membrane. The native CaJEN1 was not functional in a S. cerevisiae jen1Δ strain. Changing ser217-CTG codon (encoding leucine in S. cerevisiae) to a TCC codon restored the permease activity in S. cerevisiae, proving that the CaJEN1 gene codes for a monocarboxylate transporter.